Eating Habits and Coping Strategies for Stress in Medical Training - Nathalia Campos; Justhyn F. Loor; Gina Y. Mendoza; Nayeli Y. Tejena; Odalis N. Vera; Mario A. García (Journal of Health Science and Medical Therapy, 2026)
Academic stress is associated with dietary and lifestyle disturbances in university students, which can potentially impact their health and performance. This study examined the relationship between academic stress, eating habits, physical activity, and coping strategies among medical students at the Universidad San Gregorio de Portoviejo in Ecuador. A descriptive cross-sectional study was conducted in January 2025 with 137 students from all semesters. Two structured surveys were administered to estimate academic stress and eating habits, respectively. The majority (79.3%) consumed food outside of main meals, preferring products high in sugar and fat. Additionally, 46.6% increased their intake under stress, while 53.4% reduced it. Only 30.5% engaged in physical activity at least once a week. Passive strategies (social media, television) for coping with stress prevail, reinforcing unhealthy eating patterns. Academic stress influences the selection and frequency of food intake, favoring the consumption of ultra-processed foods and reducing physical activity. The design of nutritional education and stress management programs for medical students is recommended to improve their overall well-being.